Synthesis and characterization of porous carbon composite derived from biomass waste for supercapacitor application / Sim Cheng Kim - Sim , Cheng Kim (2020)
Energy storage devices have gradually dominated human daily activities and indispensable to economy development such as supercapacitor and battery. There are few factors determining the performance of supercapacitor and active material is one of the crucial. Therefore, biomass such as pineapple peel (PP) and green waste (GW) were preferred and prior mixed with manganese and tin carbonate to synthesize carbon composite (PP/GW-ZMO and PP/GW-ZTO) via combustion. Brunauer–Emmett–Teller (BET) was employed to study the textural properties with the highest specific surface area obtained in PP-C (1765.92 m2g-1) and GW-C (1613.92 m2g-1). The existence of composite materials was examined using x-ray diffraction (XRD), energy-dispersive x-ray spectroscopy (EDX) and transmission electron microscopy (TEM). Field emission scanning electron microscopy (FESEM) results indicated weight ratio of composite materials have altered the morphology structure. Electrochemical studies implied that carbon composite materials derived from GW exhibited better specific capacitance such as GW-ZMO1 and GW-ZTO1 achieved 123 Fg-1 and 104 Fg-1 at 0.3 Ag-1, respectively. Symmetrical cells were fabricated to examine the device’s performance. Stability test implied that devices fabricated from both porous carbon and carbon composites were steady after 5000 cycles at 0.3 Ag-1 with capacitance retention more than 85 %. Nevertheless, PP-C exhibited poor durability which it dropped drastically to almost null specific capacitance while PP-ZMO1, PP-ZTO1, GW-ZMO1 and GW-ZTO1 retained 65 %, 88 %, 79 % and 106 %, accordingly after 900 cycles of varies current densities.